Ultrasound Speckle Tracking Method Based on Gradient Optical Flow to Quantify Small Longitudinal Displacement, Shear and Longitudinal Strain in Peripheral Nerves - Snoj, Žiga; Omejec, Gregor; Javh, Jaka; Umek, Nejc (Ultrasound in medicine & biology, 2025)
This study aimed to develop, validate and test the clinical feasibility of ultrasound (US) speckle tracking method based on gradient optical flow for quantifying small longitudinal displacements, shear and strain in peripheral nerves. The speckle tracking method was validated using seven thawed, fresh-frozen isolated cadaveric forearms. Longitudinal motion of the median nerve was captured using a high-frequency 22 MHz linear probe. An air bubble marker was inserted as a reference point for manual measurement comparison. The precision and accuracy of the method were assessed by comparing manual and automatic measurements. Clinical feasibility was tested on eight healthy subjects, measuring the longitudinal displacement of the median nerve during elbow extension and shoulder anteflexion. The method demonstrated linearity, high precision and accuracy, particularly with a backtrace of five frames, reducing the displacement underestimation to 4%. In cadaveric models, the highest shear strain was observed at the nerve-tissue interfaces. In healthy subjects, the mean displacement of the median nerve was 3.3 ± 1.0 mm, with good inter-rater reliability (intraclass correlation coefficient = 0.87). The US speckle tracking method based on gradient optical flow effectively quantifies small longitudinal displacements and shear strain in peripheral nerves, with high precision and accuracy. However, the method could not detect longitudinal strain in nerves within the range of tested displacements. Future studies should investigate its applicability to smaller and deeper nerves and its usefulness in different pathological conditions.